Academic Integrity across the Canadian Landscape - McKenzie, Amanda M (Canadian Perspectives on Academic Integrity, 2018)
In the early 1990s, educators concerned about academic integrity (AI) in the United States began to collaborate on issues in this area and later established the Center for Academic Integrity, now known as the International Center for Academic Integrity (ICAI). In recent years, ICAI Canada, an offshoot of the ICAI, was created to nurture AI best practices across the nation. This article details the development of the Canadian branch of the ICAI and examines what AI looks like across Canada. In summary, future directions at these levels are examined as well as ways to further promote AI in Canada.